The Role of "Business Model Canvas" (BMC) In Improving Omzet, Comparative Analysis Approach of Beginner Enterpreneurs in the Field of Creative Economy - Kusumawati, Yuli Noor; Mulyani, Endang (Eduvest - Journal of Universal Studies, 2024)
An established business must first have a comprehensive plan, including a vision, mission, and goals to be achieved, including increasing turnover and profits and then be able to map out what the company wants and needs with its resources. BMC Strategic Planning (BMC) is a business plan model that explains goals, capital, and efforts to achieve your goals comprehensively. This planning strategy effectively minimizes failure because all risks have been mapped. In some startups, formulating a BMC is a necessity, considering that most startup companies have a risk of failure in the first 5 years. Therefore, this research wants to see the extent of BMC's role in increasing the turnover of novice entrepreneurs in creative industries that have been established for 5 years by comparing turnover before and after using BMC for 3 consecutive years. The results show that the application of BMC to budding entrepreneurs in the creative economy sector has increased their turnover by 22.82% compared to before using BMC. The highest increase in turnover was in the culinary sector, reaching 26.36%, followed by F&B at 25.05%, fashion at 23.9%, and beverages at 22.74%. The BMC elements are dominant because they prioritize the quality of taste (food and drinks) as well as the quality of packaging and clothing design, key activities, and key partners to build value propositions, then supported by accurate market segmentation and customer relationships followed by intensive promotion (Channel) so that a revenue stream occurs, in the form of increased sales (Omzet).